The Position of Leaning Forward to Reduce Breathing of COPD Patients: Literature Review - Aat Djanatunisah; Riri Maria (Unit Penelitian dan Pengabdian Masyarakat STIKES Fatmawati Jakarta, 2021)
COPD patients often experience shortness of breath as a result of inflammation in the lungs that develops in the long term. COPD is generally characterized by difficulty breathing, coughing with phlegm, and wheezing or wheezing. In this condition, the patient often finds a comfortable position to reduce shortness of breath. The aim of this study was to look at appropriate and effective interventions in reducing spasms in COPD patients. This literature study was created by analyzing scientific articles, at least in retrospective research from 2012 to 2020 and in English. Data obtained from databases include Pubmed, CINAHL, Scopus, Proquest and Google Scholar with the keywords position for breathing in COPD, position forward lean trunk for short breathing in COPD, and best position for COPD. The results of this literature obtained 5 articles that match the inclusion and exclusion criteria. The results have been found that the forward leaning position is effective in reducing shortness of breath in COPD patients because of the involvement of the respiratory accessory muscles so that the pulmonary ventilation process is good.